Love wins : A Book About Heaven, Hell, and the Fate of Every Person Who Ever Lived - Bell, Rob, 1970- (London Collins, 2011)
"Bestselling author of VELVET ELVIS and the 2 million-plus selling Nooma videos, Rob Bell, reveals a secret deep in the heart of millions of Christians-they don't believe what they have been taught are the essential truths of their faith. Out of respect for their tradition, they keep quiet, confiding to a few close friends their doubts and questions about salvation, Jesus, and, of course, God. Is Jesus really the only way into heaven? Is God "good" if he is planning on sending billions of people to eternal torment in hell? Are Christians the only ones who have it "right," and everyone else is just deceived? Bell brings out to the open and faces squarely the questions on everyone's mind: Does it really make sense that God is a loving, kind, compassionate God who wants to know people in a personal way, but if they reject this relationship with Jesus, they will be sent to hell where God will eternally punish them forever? In LOVE WINS, Bell goes to the heart of these issues and argues that the church's traditional understanding of heaven and hell is actually not taught by the Bible. Bell is emphatically not offering a new view of heaven and hell-instead, he closely examines every verse in the Bible on heaven and hell and shows what they really teach. And he discovers that Jesus's most fundamental teaching about heaven and hell is, "Love wins.""--
Keywords: Faith; Salvation -- Christianity; Trust in God; RELIGION / General